An Alternative for the External Debt with the Implementation of Islamic Financial Instrument: Study on Indonesia Deficit Budget Policy - Putri Rizka Citaningati; Kamaluddin Kamaluddin (Jurnal Keuangan dan Perbankan, 2022)
Indonesian government tends to use a budget deficit policy which has an impact on the amount of the state budget being no larger than the revenue earned by the state. This certainly triggers the government to incur debt, especially foreign debt. Indonesia as a country with a majority Muslim population certainly has great potential in utilizing Islamic financial instruments as a substitute for foreign debt. Therefore, this study aims to examine good state budget policies in avoiding state debt through the implementation of Islamic financial instruments such as zakat and waqf. The paper uses a descriptive qualitative approach. This study uses secondary data on state revenues, state expenditures, the state budget deficit, and Indonesia's sovereign debt in 2016-2020. The data were analyzed descriptively to determine the negative impact of Indonesia's current foreign debt. The result concludes that Islamic financial instruments such as zakat and waqf can be used as an alternative to foreign debt. In addition, the government can also issue SBSN, such as Sukuk, which encourage public confidence to invest in the government